Identidades plurais e o cotidiano da escola - Soligo, Marina Guazzelli (2005)
From the day-by-day lived at school, this dissertation proposes to understand how teenager students (12 to 14 years old), Stage II of Ensino Fundamental, constitute cultural identities within a closed conection to midia and youth cultural, at the same time that they reject the school cultural world. It questions about the nature of the teenager students cultural manifestations, by questioning in what extent these manifestations constitute cultural identities and own styles that resist to new forms of power, typically of a society of control. Hence, it was carried out a case study of a Council Secondary School from the West zone of São Paulo. With respect to the studied object, the research had the following hypotheses: a) the teenager students demotivation, related to the teaching and learning processes done in the classroom, translates in a rejection to the actual school behaviour model and justifies the actual crisis; b) the teenagers try to get far from the cultural world offered by the school and conect themselves to the youth cultural by the midia mediation, particularly by the radio mediation, TV and CDs, by seeking different cultural identities from those offered by the school and by the family; c) these identities relate to today , the present, and they deny the past as well as a future perspective; d) it is possible of noticing dimensions of resistance, according to De Certeau, about the constitution of these identities related to new forms of actual power in our society. The field research work showed enough elements that confirmed the hypotheses. The seek of colective identities that identify them to the reference group and make them different to other society groups, including other teeanager groups, showed extremely strong among students. For this reason, they make an effort to what they consider cultural manifestations and own style of youth cultural, linked to the consume